Increased mortality persists in an adult drug-resistant epilepsy prevalence cohort. Issue 10 (19th February 2014) - Callaghan, Brian; Choi, Hyunmi; Schlesinger, Malka; Rodemer, William; Pollard, John; Hesdorffer, Dale C; Hauser, W Allen; French, Jacqueline
Abstract : Objective: To investigate the cumulative probability of death and the standardised mortality ratio (SMR) in an adult drug-resistant epilepsy (DRE) population. Methods: In two separate centres during 2003–2006, we identified a total of 433 patients with DRE defined as at least one seizure per month and failure of at least two antiepileptic drugs. These patients were subsequently followed for a total follow-up of 6 years. We examined the cumulative probability of death, using Kaplan-Meier methodology, and the SMR based on mortality data from the Social Security Death Index. Clinical predictors of death were evaluated using Cox regression analysis. Results: The cumulative probability of death was 8.7% (95% CI 6.2% to 12.1%) at 6 years. The overall SMR was 2.4 (95% CI 1.7 to 3.3). It was 3.1; 95% CI 2.0 to 4.6 in subjects with remote or progressive aetiology and 1.7; 95% CI 0.8 to 2.8 in subjects with unknown aetiology. The SMR was significantly increased in those with a known remote aetiology (2.5; 95% CI (1.4 to 3.8)). Older age at enrolment and symptomatic generalised epilepsy syndrome were significant predictors of death. Discussion: Mortality is increased in this drug-resistant population; largely driven by those with a known epilepsy aetiology. The increased mortality remains even after exclusion of those with a progressive aetiology. Previous studies of incident epilepsy cohorts revealed increased mortality that declines to near-normal levels after the first several years, but in our DRE cohort, mortality remains elevated despite a median duration of epilepsy of 25 years at study entry.